Phylogenetic investigation of Dengue Virus Type 2 isolated in Malaysia - Chee, H.Y.; AbuBakar, Sazaly (2003)
Dengue virus type-2 (DEN-2) has been isolated in Malaysia for more than three decades. The virus caused two major outbreaks in the early 1990s and late 1990s. Phylogenetic analyses performed using available E/NS1 junction sequences identified two DEN-2 genotypes: DEN-2 Asian 1 and DEN-2 Cosmopolitan. DEN-2 Cosmopolitan/Malaysia is the predominant genotype comprising more than 80 of the total isolates. Two different clades of DEN-2 Cosmopolitan/Malaysia genotype were identified. Clade I consisted of mainly the older isolates, whereas Clade II consisted of the more recent isolates, including that responsible for both the major DEN-2 outbreaks. Two different strains of DEN- 2 Cosmopolitan/Malaysia genotype were involved in the outbreaks, yet both strains appeared to share a common ancestral lineage with isolates from the early 1970s. Isolates from the late 1990s showed higher sequence similarities to the late-1960s isolates than the early-1990s isolates. These findings raised the possibility that the different DEN-2 strains noted over the last three decades in Malaysia might have evolved from a pre existing DEN-2 gene pool.